Miniaturized immunoassays: moving beyond the microplate. (January 2012) - Verch, Thorsten; Bakhtiar, Ray
After more than 40 years, immunoassays are still the backbone of protein biomarker analysis in clinical diagnostics and drug development. They have come a long way since their inception, incorporating technical developments including monoclonal antibodies, novel labels and lately microfluidics. A number of microfluidic platforms have been tested, such as centrifugational compact disc assays, lab-on-a-chip, arrays and digital electrochemical assays. This review focuses on commercial applications of microfluidic immunoassays with reference to some applied academic examples of interest. Advantages and disadvantages of the platform technologies are discussed in general.